Visible light-assisted charge extraction in high-band-gap SrTiO3 through the integration of a triplet sensitizer−emitter thin film - Jie, Kelvin V. Y.; Ahmad, M. Fairus; Mohmad, A. Rahman; Ismail, A. Mawardi; Norizan, M. Natashah; Ramli, M. Mahyiddin; Shaari, Safizan; Sulaiman, Yusran; Rais, Shamsul A. A.; Johari, Shazlina (American Chemical Society, 2024)
A challenge in PV designs, including those with an electron transport layer (ETL), is the presence of ‘parasitic absorbers’. These are layers that absorb light without significantly converting it to electrical current, impacting the total external quantum efficiency (EQE). Strontium titanate (STO), a high-band-gap (3.20 eV) perovskite metal oxide, holds promise as an electron transport layer (ETL) for solar energy harvesting. Despite STO’s potential, it primarily operates in the UV spectrum, not fully utilizing the broader light range, and hence can be the source of parasitic absorbers. In this study, we report a significant enhancement in the EQE of STO through the integration of a triplet sensitizer–emitter (TSE) system, designed to upconvert the visible spectrum into UV light and improve the charge extraction from STO. The TSE system uses carbazolyl dicyanobenzene (4CzIPN) as a sensitizer and p-terphenyl (TP) as an emitter. To investigate the EQE of such a system, we fabricate STO as a PV cell. The revised PV cell architecture (ITO/TiO2/STO/TSE/PEDOT:PSS/Al) is a modification of the conventional configurations (ITO/TiO2/STO/PEDOT:PSS/Al). With the TSE thin film, the modified STO PV cell shows better charge extraction under sunlight compared to the standard STO PV cell, indicating that the upconversion process can enhance the hole conductions from STO to PEDOT:PSS through the TSE system. We noted an EQE increase with intense light of λ > 345 nm in thicker TSE layers and a decrease in the EQE under similar light intensity in thinner TSE layers. The Kelvin probe force measurement (KPFM) data showed that the TSE layer receives holes from STO under illumination. Additionally, time-resolved photoluminescence (TRPL) experiments showed that the TSE/STO thin film is able to produce UV emission after irradiation with lower energy light. Then, the EQE variation in thicker TSE layers under intense irradiation can be attributed to the solid-state upconversion, indicating its thickness-dependent performance. These findings underline the strategies for maximizing the utilization of the solar spectrum in PV applications.